Implementasi Program Padat Karya: Studi Kasus tentang Pelaksanaan Program Padat Karya di Kelurahan Ciracas Kecamatan Ciracas Jakarta Timur - Rahaju, Tjitjik (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2007)
This article describes about the implementation of â€œPadat Karyaâ€ programme in Ciracas, East Jakarta. It is based on a study conducted through case study approach. This study, on the ather side, is conducted based on global economic crisis occured in Indonesia since many years ago. Social Safety Net programme is one of solutions implemented to overcome the crisis in Indonesia. This article wil try to analyze some aspects related to implementation of the programme of â€œPadat Karyaâ€, indicators, and some factors that affected the implementation of the program. Kata Kunci: Program Padat Karya, krisis ekonomi, Jaring Pengaman Sosial, kemiskinan